Peter C. Petersen letter to Nicholas S. Halmi regarding bird sightings and bird banding, November 29, 1977 - Petersen, Peter C.et al (1977)
Field notes contributed by Peter C. Petersen in a letter to Nicholas S. Halmi. The field notes include a report with Flycatcher, Thrush, Vireo and Warbler migration birds banded. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1977. Epson - sheet feed/flatbed